EVOLUCIÓN DE LA POLÍTICA EXTERIOR DE COSTA RICA - Facio S., Gozalo J. (2015)
International situations have a growingforce over the internal political events of anycountry, wich is very important to take theminto account to reach the basic concepts of domesticpolicy.